NOD mice exocrinopathy: towards a neuroimmune link - Calafat, Mario Jose (2007)
Sjogren's syndrome (SS) is a chronic autoimmune disorder of exocrine glands characterized as an autoimmune exocrinopathy and more specifically as an autoimmune epithelitis. An impaired balance of neuroimmune interactions mediated by vasoactive intestinal peptide (VIP) in the target organ at early stages of disease is explored by means of the nonobese diabetic (NOD) mouse model of SS. We have previously described a reduced salivary secretion and signaling upon VIP stimulation. The effect reflected a differential regulation of the neural isoform of nitric oxide synthase by calcium calmodulin kinase II and occurred prior to the appearance of detectable levels of cytokines in NOD glands. VIP acting on NOD macrophages treated with lipopolysaccharide promoted anti-inflammatory effects by inhibiting nitric oxide synthase induction as well as IL-12 and TNF-alpha production, while stimulating IL-10. Here we present evidence on the ability of apoptotic acinar cells from submandibular glands of NOD mice to stimulate nitric oxide in both peritoneal and glandular macrophage pools to a similar extent as lipopolysaccharide + IFN-gamma. VIP was not effective to prevent nitrite accumulation and modestly increased IL-10 levels in macrophages coincubated with acinar cells. An enhanced nitrite response of NOD glandular macrophages in basal and stimulated conditions compared to peritoneal cells is also shown